Gender equality results case study India infrastructure development investment program for tourism in Himachal Pradesh and Punjab. (Gender equality results case studies.)
The program has contributed to economic growth, and provides evidence of the capacity of gender responsive tourism development to promote community participation in tourism and enhance the status of women. This report looks at results in three areas: human capital and economic empowerment, the creation of spaces for women voices to be heard, and the promotion of equal rights. The case study affirms that a gender inclusive design, coupled with effective implementation, gives women and men equal access to project benefits.